A cross-cultural comparison of visual landscape preferences for the natural environment - Mohd-Shariff, Mustafa Kamal Bin, author; Haas, Glenn E., 1951-, advisor; Wallace, George E., committee member; Lakey, Jeff, committee member; Taylor, Jonathan G., committee member (Colorado State University. Libraries, 1994)
The purpose of this study was (1) to identify significant differences in the landscape preferences for the natural environments of Caucasian, Hispanic, Black, Native, and Asian American students at Colorado State University, (2) to identify and compare the underlying perceptual dimensions of their preferences, and (3) to compare the effectiveness of the Kaplans' Informational Processing Model of Environmental Preferences predictors on the landscape preferences of each group. The study found that all groups rated the mountain category highest and the grassland category lowest. However, within categories, Native Americans and Caucasians rated mountain and grassland categories significantly higher than Blacks or Asians. Though there were no statistically significant differences, Blacks and Asians rated the city park category relatively higher than Native Americans and Caucasians. Hispanics did not show significant differences from any other group in this study, in mean preference ratings for any of the three environment types depicted. Four perceptual dimensions were found in the mountain category. These were labelled (1) Partially Screened Views, (2) Rock Formations, (3) Enclosed Views, and (4) Exposed Rocks. In the grassland category, there were only two perceptual dimensions - (1) Pathways and (2) Buttes/ Escarpments. Some significant group differences were noted among these dimensions. In utilizing the Kaplans' Informational Processing Model of Environmental Preference, it was found that Complexity and Mystery correlated highly with the landscape preferences of all groups. A multiple regression analysis of the predictors found that they have significant effects on the preferences of all groups and predicted the preferences of all groups, except for Blacks, in similar manner.
Keywords: Landscapes; Nature (Aesthetics)